On the observed and simulated responses of the extratropical atmosphere to surface thermal forcing - Wills, Samantha M., author; Thompson, David W. J., advisor; Alexander, Michael, committee member; Barnes, Elizabeth, committee member; Maloney, Eric, committee member; Venayagamoorthy, Subhas Karan, committee member (Colorado State University. Libraries, 2019)
The ocean is an integral part of the climate system, and its closely-coupled interactions with the atmosphere system have wide-ranging impacts on the large-scale and local patterns of climate and weather variability from one region of the globe to another. Improvements in the resolution of satellite observations and numerical models over the past decade have led to a series of advances in understanding the role of the ocean in extratropical air-sea interaction. While the influence of the extratropical ocean can be relatively subtle and difficult to detect, recent studies have provided a growing body of evidence suggesting that the extratropical ocean has a potentially important influence on the atmospheric circulation on a wide variety of timescales. The aim of this thesis is to improve the current understanding on the role of the extratropical ocean in climate by 1) presenting new observational analyses on the relationships between midlatitude SST anomalies and the atmospheric circulation on subseasonal timescales and 2) providing a new, simplistic framework for interpreting the atmospheric response to surface thermal forcing across the globe in an idealized global climate model. In the first theme of this thesis, observational analyses of daily-mean data are exploited to re-examine the evidence for midlatitude air-sea interaction over the Kuroshio-Oyashio Extension region, and important comparisons are drawn to a previous companion study over the Gulf Stream Extension region. The results indicate that during the boreal winter season, SST anomalies in both the Gulf Stream and Kuroshio-Oyashio Extension regions are associated with distinct spatial and temporal patterns of atmospheric variability that precede and follow peak amplitude in the SST field on daily-mean timescales. In particular, a very similar pattern of low pressure anomalies that develops over the warm SST anomalies is viewed as the most robust common aspect of the atmospheric "response" over both ocean basins. The least common aspect of the "response" is characterized by robust high pressure anomalies that develop over the North Atlantic and have a seemingly unique relationship to positive lower-tropospheric temperature anomalies generated over the Gulf Stream Extension region. These results suggest that extratropical SST anomalies on subseasonal timescales are capable of forcing significant changes in the large-scale atmospheric circulation through the transfer of heat from the ocean to the atmosphere. Partially motivated by the results from the observational analyses, the second theme of this thesis presents a simplified model framework to critically assess the one-way influence of the ocean on the atmosphere at different locations across the globe. A series of steady-state and transient numerical experiments are designed to explore the atmospheric response to surface thermal forcing in an idealized "aquaplanet" configuration of the NCAR Community Atmosphere Model, Version 5.3. The results indicate that in each of the extratropical SST perturbation experiments, there is a consistent and robust steady-state atmospheric response (of similar sign and amplitude) to surface thermal forcing. The response is characterized by a hemispheric-scale, equivalent-barotropic pattern of atmospheric circulation anomalies reminiscent of the model's leading mode of internal variability and is seemingly independent of the latitudinal placement of the heat source. This result is explored further, and a possible explanation of the consistent steady-state atmospheric circulation response is discussed.